(untitled) (Communications in Computational Physics, 2013)
The structural and functional description of protein-protein complexes and their comprehension is a key concept, not only to increase the scientific knowledge in basic terms but also for the application to the biomedical and pharmaceutical industry. The binding association between proteins is nowadays attribute to a few key residues at the interface – the hot-spots. The complex between the RNase inhibitor (RI) and RNaseA protein provides an excellent system to study the role of the functional epitope as it is essential in various molecular recognition processes and constitute one of the tightest complexes known. An energetic pattern of the interface is accomplished by computational alanine scanning mutagenesis and a dynamical characterization is accomplished by a detailed study of the molecular dynamical simulations. A special emphasis is given to the role of solvation across the interface and the shielding of warm- and hot-spots from water.